Contested Hegemony: The Great War and the Afro-Asian Assault on the Civilizing Mission Ideology - Adas, Michael (Journal of world history, 2004)
Perhaps the most fundamental and enduring effects of the worldwide crisis of the European colonial order brought on by the Great War of 1914-1918 resulted from the challenges it provoked on the part of Asian and African novelists, poets, philosophers, and emerging political leaders. Four years of indecisive, mechanized slaughter on the Western Front gave rise to spirited and widely publicized critiques of the civilizing mission ideology that had long been invoked to justify European dominance. Since at least the early nineteenth century, the credibility of the civilizing mission credo for European colonizers as well as subject peoples depended increasingly on its emphasis on the unprecedented superiority that Europeans had attained in science and technology over all other peoples and cultures. Some Indian and African, and indeed also European, intellectuals had challenged these gauges of European racial and historical preeminence in the decades before 1914. But the appalling uses to which European discoveries and inventions were put in the First World War raised profound doubts among intellectuals across four continents about the progressive nature of industrial civilization and its potential as the model for all of humanity to emulate. The highly contentious exchanges that these questions gave rise to in the postwar decades soon coalesced into arguably the first genuinely worldwide discourse and proved a critical prelude to the struggles for decolonization that followed.